2018
DOI: 10.15406/ijh.2018.02.00102
|View full text |Cite
|
Sign up to set email alerts
|

Phytomelatonin: a comprehensive literature review and recent advance on medicinal meadow

Abstract: Melatonin (N-acetyl-5-methoxytryptamine), a well-known pineal gland hormone, was discovered in plants in 1995 but till then very little research into it has been carried out in this arena. It is present in different parts of all the plant species studied, including leaves, stems, roots, fruits and seeds. Based on the ubiquitous distribution of melatonin in all kingdoms, melatonin was even suggested as the nature's most versatile biological signal molecule. Since the identification of melatonin in plants by Hat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…MEL is an alkaloid compound that has a bitter and unpleasant taste, which helps in protecting plants against herbivores [ 143 ]. Plants with high levels of MEL, such as walnut, if consumed by herbivores, can increase the level of MEL in their bodies and disturb their physiology [ 144 ]. The resistance of rice plants to herbivores, such as leaffolder and brown planthopper, was significantly enhanced via the production of JA, SA, MEL, flavonoids, and lignin [ 120 ].…”
Section: Role Of Mel In the Mitigation Of Biotic Stressesmentioning
confidence: 99%
“…MEL is an alkaloid compound that has a bitter and unpleasant taste, which helps in protecting plants against herbivores [ 143 ]. Plants with high levels of MEL, such as walnut, if consumed by herbivores, can increase the level of MEL in their bodies and disturb their physiology [ 144 ]. The resistance of rice plants to herbivores, such as leaffolder and brown planthopper, was significantly enhanced via the production of JA, SA, MEL, flavonoids, and lignin [ 120 ].…”
Section: Role Of Mel In the Mitigation Of Biotic Stressesmentioning
confidence: 99%
“…In 2018 Bhattacharjee & Dey published a literature review discussing phytomelatonin or plant based sources of melatonin, and S. baicalensis is a source of the hormone. 81…”
Section: Phytomelatoninmentioning
confidence: 99%
“…In the development and progression of all the diseases mentioned above, numerous molecules such as naphthodianthrones, acyl-phloroglucinols, flavonoids and xanthones are involved [9]. Melatonin (N-acetyl-5-methoxytryptamine) is a powerful antioxidant molecule involved in the neurodegeneration process typical of Alzheimer's and Parkinson's, and is also used to treat insomnia typical in depressed patients [17]. Melatonin has been detected in numerous plant species, in particular, different authors have reported the presence of melatonin in H. perforatum [18][19][20].…”
Section: Introductionmentioning
confidence: 99%